Phase I study of the mitomycin C analogue BMS-181174. - Macaulay, V. M. (Nature Publishing Group, 1998)
BMS-181174 is an aminodisulphide derivative of Mitomycin C (MMC) with activity against a range of tumour cell lines and xenografts, including MMC-resistant tumours. In a phase I study of 82 patients with confirmed malignancy, we administered BMS-181174 at doses of 0.8-75 mg m(-2) by intravenous injection every 28 days. At least three patients were evaluated at each dose level, and 174 courses were administered. The pharmacokinetics were dose linear at BMS-181174 doses of 11.5-75 mg m(-2) and the drug appeared to undergo wide distribution. The maximum-tolerated dose was 65 mg m(-2) in previously treated patients and 75 mg m(-2) in chemotherapy-naive cases. The dose-limiting toxicity was myelosuppression, particularly thrombocytopenia, which was prolonged and cumulative. Three patients treated at 65-75 mg m(-2) died suddenly with evidence of pneumonia/pneumonitis, thought to be drug-related. Other toxicities included thrombophlebitis, possible cardiotoxicity (asymptomatic, reversible decline in left ventricular function) and renal impairment. The partial response rate was 5% (4 out of 82) overall, and 9% (3 out of 32) in patients treated at 65-75 mg m(-2). Responses occurred in treated and previously-untreated patients, including cases of colorectal cancer, non-small-cell lung cancer, ovarian cancer and adenocarcinoma of unknown primary site. BMS-181174 has anti-cancer activity but, because of its toxicity, particularly pneumonitis and thrombophlebitis, no phase II studies are planned.